Disrupted Oxytocin-Appetite Signaling in Females With Anorexia Nervosa - Aulinas, Anna (J Clin Endocrinol Metab, 2019)
CONTEXT: In healthy females, oxytocin levels decrease postmeal, corresponding to increased satiety. The postprandial response of oxytocin in females with anorexia nervosa (AN)/atypical AN is unknown. OBJECTIVES: To determine the pattern of postprandial serum oxytocin levels in females with AN/atypical AN, relationship with appetite, and effect of weight, eating behavior, and endogenous estrogen status. DESIGN: Cross-sectional. SETTING: Clinical research center. PARTICIPANTS: 67 women (36 with AN [<85% expected body weight (EBW)]; 31 with atypical AN [≥ 85% EBW)]), age 22.4 ± 0.9 (mean ± SEM) years, categorized by weight, restricting vs binge/purge behavior, and estrogen status. INTERVENTIONS: Standardized mixed meal. MAIN OUTCOME MEASUREMENTS: Blood sampling for oxytocin occurred fasting and 30, 60, and 120 minutes postmeal. Subjective appetite was assessed using visual analog scales. RESULTS: In females with AN/atypical AN, oxytocin levels decreased from fasting to 60 (P = 0.002) and 120 (P = 0.005) minutes postmeal. The decrease in oxytocin from fasting to 120 minutes was greater in females with atypical AN than AN (P = 0.027) and did not differ by restricting vs binge/purge behavior or estrogen status. Controlling for caloric intake, the decrease in oxytocin was inversely related to the decrease in hunger postmeal in females with atypical AN (P = 0.04). CONCLUSIONS: In females with AN/atypical AN, oxytocin levels decrease postmeal, as established in healthy females. Weight, but not restricting vs binge/purging nor endogenous estrogen status, affects postprandial oxytocin levels. The postprandial change in serum oxytocin levels is related to appetite in females with atypical AN only, suggesting a disconnect between oxytocin secretion and appetite in the undernourished state.